Violent Hard X-ray Variability of Mrk 421 Observed by NuSTAR in 2013 April - Paliya, Vaidehi S; Bottcher, Markus; Diltz, Chris; Stalin, C S; Sahayanathan, S; Ravikumar, C D (arXiv.org, 2015)
The well studied blazar Markarian 421 (Mrk 421, \(z\)=0.031) was the subject of an intensive multi-wavelength campaign when it flared in 2013 April. The recorded X-ray and very high energy (VHE, E\(>\)100 GeV) \(γ\)-ray fluxes are the highest ever measured from this object. At the peak of the activity, it was monitored by the hard X-ray focusing telescope {\it Nuclear Spectroscopic Telescope Array} ({\it NuSTAR}) and {\it Swift} X-Ray Telescope (XRT). In this work, we present a detailed variability analysis of {\it NuSTAR} and {\it Swift}-XRT observations of Mrk 421 during this flaring episode. We obtained the shortest flux doubling time of 14.01\(±\)5.03 minutes, which is the shortest hard X-ray (3\(-\)79 keV) variability ever recorded from Mrk 421 and is on the order of the light crossing time of the black hole's event horizon. A pattern of extremely fast variability events superposed on slowly varying flares is found in most of the {\it NuSTAR} observations. We suggest that these peculiar variability patterns may be explained by magnetic energy dissipation and reconnection in a fast moving compact emission region within the jet. Based on the fast variability, we derive a lower limit on the magnetic field strength of \(B \ge 0.73 δ_1^{-2/3} \, ν_{19}^{1/3}\)~G, where \(δ_1\) is the Doppler factor in units of 10, and \(ν_{19}\) is the characteristic X-ray synchrotron frequency in units of \(10^{19}\)~Hz.